Pemilihan Kartu Seluler Internet Sebagai Pendukung Proses Pembelajaran Dengan Metode Analytic Hierarchy Process - Ririn Wahyu Arida (Universitas Islam Kadiri, 2018)
This research used the method of AHP by manual assisted with programs EXCEL for its calculations. AHP can help solve complex problems and is not structured into groups then the groups will enter into a hierarchy. With the help of AHP so students can choose mobile internet cards are good in supporting the learning process. From the results obtained in the calculation results as follows: 1. the paired comparison between calculation Results variable in choosing a mobile card on top of the obtained weights 0.13 to signals, weights, 0.21 to 0.66, the price for the location. This means that the location is the main criteria in decision making cards seluer internet with weights of 0.66%. Followed by the signal with weights 0.21% and prices with weights 0.13%; 2. the data processing Results in getting the main alternative for a mobile internet card is Indosat with a value of 0.508, followed by Simpati with the values of 0.256. And currently third XL/Axis value of 0.232